Unpacking the collection networks of material and social agency in the museum - Byrne, Sarah; Clarke, Anne.; Harrison, Rodney; Torrence, Robin; SpringerLink (Online Service). (New York Springer, 2011)
Museum collections are often perceived as static entities hidden away in storerooms or trapped behind glass cases. By focusing on the dynamic histories of museum collections, new research reveals their pivotal role in shaping a wide range of social relations. Over time and across space the interactions between these artefacts and the people and institutions who made, traded, collected, researched and exhibited them have generated complex networks of material and social agency.In this innovative volume, the contributors draw on a broad range of source materials to explore the cross-cultural interactions which have created museum collections. These case studies contribute significantly to the development of new theoretical frameworks to examine broader questions of materiality, agency, and identity in the past and present.Grounded in case studies from individual objects and museum collections from North America, Europe, Africa, the Pacific Islands, and Australia, this truly international volume juxtaposes historical, geographical, and cross-cultural studies.This work will be of great interest to archaeologists and anthropologists studying material culture, as well as researchers in museum studies and cultural heritage management.
Electronic reproduction.
Keywords: Ethnological museums and collections -- Social aspects; Ethnological museums and collections -- Research; Material culture -- Social aspects; Material culture -- Research; Museums -- Collection management -- Social aspects; Museum exhibits -- Social aspects; Electronic books